Effects of pretreatment, sowing time, sowing environment and climate factors on germination in Acer pseudoplatanus L. Utjecaj predsjetvene pripreme, vremena sjetve, zaštićenog prostora i klimatskih čimbenika na klijavost sjemena vrste Acer pseudoplatanus L. - Yücesan, Zafer (Array, 2021)
In this study, the effects of different sowing environment (greenhouse and nursery), pretreatment (cold moist stratification), different sowing time (autumn, spring and summer) and some climate factors (air temperature, relative air humidity, soil temperature and soil moisture) on the germination of Acer pseudoplatanus L. seeds were studied. Seeds were harvested from the tree located in the Karadeniz Technical University campus. Three different germination trials were carried out; (1) direct sowing in autumn after seed collection (Control), (2) sowing stratified seeds in spring (Stratification-1) and (3) sowing stratified seeds in summer (Stratification-2). During the germination trial processes, air temperature, relative air humidity, soil temperature and soil moisture were measured periodicaly. Thus, the germination percentage changes in different sowing environments have been established on the basis of some climate factors. Higher germination percentages were obtained in the autumn (Control) compared to the spring (Stratification-1) and summer (Stratification-2) sowings. The highest percentages of germination were determined in the control trials (70% in greenhouse and 58% in nursery). Obtained germination results based on different sowing times revealed secondary dormancy in Acer pseudoplatanus L. seeds. It has been determined that the mean germination time in the greenhouse (12 days) was shorter than the mean germination time in the nursery (18 days). In addition, the obtained results showed that stratification and sowing time have a positive effect on the mean germination time in the greenhouse. Because of getting the best germination rates, keeping some climate factors constant (21.0-24.9 °C air temperature; 17.0-19.9 °C soil temperature; 63.0-68.9% relative air humidity; 60.0-67.9% soil moisture) during the vegetative propagation practices in the greenhouse, should affect mass seedling production in Acer pseudoplatanus L.